2014
DOI: 10.1007/s00464-014-3814-1
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic ureteral injury in colorectal cancer surgery: a nationwide study comparing laparoscopic and open approaches

Abstract: In this nationwide study laparoscopic surgery for rectal cancer with curative intent was associated with a significantly increased risk of iatrogenic ureteral injury compared to open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 25 publications
4
52
1
1
Order By: Relevance
“…In rectal cancer patients (n = 5,959), the laparoscopic approach was used in 1899 patients, of whom 19 (1.0%) sustained ureteral injuries, whereas 17 (0.42%) of 4060 patients who underwent an open resection had a ureteral injury. In multivariate analysis adjusted for age, gender, ASA score, body mass index, tumor stage, preoperative chemoradiation, calendar year, and specialty of the surgeon, the laparoscopic approach was associated with an increased risk of ureteral injury (OR = 2.67; 95% CI = 1.26-5.65) 10) . Dissection of the "white line" on the colon side in order to leave the ureter in the retroperitoneum.…”
Section: Risk Factors For Ureteric Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…In rectal cancer patients (n = 5,959), the laparoscopic approach was used in 1899 patients, of whom 19 (1.0%) sustained ureteral injuries, whereas 17 (0.42%) of 4060 patients who underwent an open resection had a ureteral injury. In multivariate analysis adjusted for age, gender, ASA score, body mass index, tumor stage, preoperative chemoradiation, calendar year, and specialty of the surgeon, the laparoscopic approach was associated with an increased risk of ureteral injury (OR = 2.67; 95% CI = 1.26-5.65) 10) . Dissection of the "white line" on the colon side in order to leave the ureter in the retroperitoneum.…”
Section: Risk Factors For Ureteric Injurymentioning
confidence: 99%
“…Conversely, in their series, there was a statistically significant increase in IUI occurring after laparoscopic versus open procedures (0.66% vs. 0.15%, respectively; p = 0.007) 4) . Andersen et al 10) reviewed the Danish National Colorectal Cancer database (DCCG) with 18,474 patients following resection for colorectal cancer. The rate of ureteral injuries in the entire cohort was 0.44%, with 37 (0.59%) injuries in the laparoscopic (n = 6,291) and 45 (0.37%) in the open group (n = 12,183) (p = 0.03).…”
Section: Risk Factors For Ureteric Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…One study based on the Danish National Colorectal Cancer database reported procedures for colorectal cancer to have an iatrogenic ureteral injury rate of 0.44 % and found a significantly higher rate of injury in the laparoscopic group compared to the open group (0.59 vs 0.37 %, p=0.03) [38]. Analysis of a nationwide 10-year inpatient sample found that ureteral injuries during colorectal surgery occur in approximately 0.28 % of cases and were found to independently be associated with higher mortality, morbidity, longer length of hospitalization, and higher hospital charges [39].…”
Section: Colorectalmentioning
confidence: 99%
“…Analysis of a nationwide 10-year inpatient sample found that ureteral injuries during colorectal surgery occur in approximately 0.28 % of cases and were found to independently be associated with higher mortality, morbidity, longer length of hospitalization, and higher hospital charges [39]. Risk factors included laparoscopic approach, rectal cancer, adhesions, metastatic cancer, malnutrition, and procedure performed at teaching hospitals [38,39].…”
Section: Colorectalmentioning
confidence: 99%